2007
DOI: 10.1111/j.1365-294x.2007.03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and processes underlying evolutionary significant units in the Platypleura stridula L. species complex (Hemiptera: Cicadidae) in the Cape Floristic Region, South Africa

Abstract: Cicadas have been shown to be useful organisms for examining the effects of distribution, plant association and geographical barriers on gene flow between populations. The cicadas of the Platypleura stridula species complex are restricted to the biologically diverse Cape Floristic Region (CFR) of South Africa. They are thus an excellent study group for elucidating the mechanisms by which hemipteran diversity is generated and maintained in the CFR. Phylogeographical analysis of this species complex using mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 83 publications
4
56
0
Order By: Relevance
“…Previous studies support the theory that historical geological and climatic events associated with the late Miocene to the Pleistocene on the CFM coincided with the drastic transformation of the population histories of terrestrial flora and inland aquatic fauna (Cowling et al, 2008;Swartz et al, 2009). In spite of this, a growing number of studies involving other taxa suggests that divergence may have occurred during the Pleistocene (Tolley et al, 2006;Daniels et al, 2007;Price, Barker & Villet, 2007;Swart et al, 2009). For example, a study investigating the divergence of terrestrial invertebrates (cicadas, Platypleura stridula), that are host-plant specific and occur on plants found near drainages on the CFM, showed that the large genetic distances between lineages were a result of the isolation of drainages, which may have reduced gene flow between drainages during the Pleistocene (Price et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies support the theory that historical geological and climatic events associated with the late Miocene to the Pleistocene on the CFM coincided with the drastic transformation of the population histories of terrestrial flora and inland aquatic fauna (Cowling et al, 2008;Swartz et al, 2009). In spite of this, a growing number of studies involving other taxa suggests that divergence may have occurred during the Pleistocene (Tolley et al, 2006;Daniels et al, 2007;Price, Barker & Villet, 2007;Swart et al, 2009). For example, a study investigating the divergence of terrestrial invertebrates (cicadas, Platypleura stridula), that are host-plant specific and occur on plants found near drainages on the CFM, showed that the large genetic distances between lineages were a result of the isolation of drainages, which may have reduced gene flow between drainages during the Pleistocene (Price et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, a growing number of studies involving other taxa suggests that divergence may have occurred during the Pleistocene (Tolley et al, 2006;Daniels et al, 2007;Price, Barker & Villet, 2007;Swart et al, 2009). For example, a study investigating the divergence of terrestrial invertebrates (cicadas, Platypleura stridula), that are host-plant specific and occur on plants found near drainages on the CFM, showed that the large genetic distances between lineages were a result of the isolation of drainages, which may have reduced gene flow between drainages during the Pleistocene (Price et al, 2007). Price et al (2007) attributed their findings of the diversification of cicadas in the Pleistocene to possible habitat philopatry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the cicada groups may contain cryptic species that will be discovered using these methods, which is a common experience in Cicadidae (e.g. Price et al 2007, Price et al 2010, Popple 2013, Marshall et al 2015, Hertach et al 2015, Wade et al 2015) especially in recently neglected biodiversity hotspots such as India. We hope that this current taxonomic update will facilitate species discovery and further systematic and ecological work on cicadas of the Indian region.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that allopatric faunal distribution may have therefore been driven by distributional changes and fragmentation of the flora as a result of climatic oscillations (Price et al, 2007;Tolley et al, 2006).…”
Section: Biogeographic Inferences and Speciation Eventsmentioning
confidence: 99%